HUBUNGAN ANTARA METODE OPERASI LICHTENSTEIN DENGAN TEPI MESH KRANIO-LATERAL DILAKUKAN OVERLAPPING DENGAN TIDAK DILAKUKAN OVERLAPPING PADA KEJADIAN RESIDIF HERNIA INGUINALIS LATERALIS - , Lizaldi Usnan ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: The main mechanism of abdominal strengthening with mesh is the fibrous tissue growth from the host into the mesh that will perfectly joint the mesh and the host tissue that will form a new layer to strengthen the abdominal wall, therefor the mesh surface that overlap and does not contact the host tissue has no function. Objective : To compare Lichtenstein operation method with overlapping kranio-lateral edge of mesh against non overlapping kranio-lateral edge of mesh on residiv event of lateral inguinal hernia. Methods : This study was done between March â August 2012 with a Kohort design. The sample are men age â¥ 40 years old that have lateral inguinal hernia and operated with Lichtenstein method. The sample was taken in RSUP Dr. Sardjito Yogyakarta and the network hospital, 30 patient that was done overlapping Lichtenstein operation and 30 patient that was done non overlapping Lichtenstein. The patient was ask to fill a questioner. Result : Out of 60 patient, was divided into 50% that was operated with non overlapping Lichtenstein method and 50% that was operated with overlapping Lichtenstein method. The logistik regretion analisis show non overlapping Lichtenstein method does not cause residiv with the OR<1. Conclusion : Logistik regretion analisis determine the hipotesis is accepted, that is Lichtenstein non overlapping operation method does not cause residiv. Lichtenstein non overlapping operation method have a lower residiv event and is not a residiv risk factor of lateral inguinal hernia (OR=<1)